Study of carotenoids and chlorophylls content in Thymus L. essential oils genus species at the reproductive period - Mazulin, O. V.; Fukleva, L. A.; Steshenko, Ya. M.; Mazulin, G. V.; Salii, O. O.; Puchkan, L. O.; Мазулін, Олександр Владиленович; Фуклева, Лариса Анатоліївна; Стешенко, Яна Миколаївна; Мазулін, Георгій Владиленович; Салій, О. О.; Пучкан, Любов Олександрівна (My University, 2023)
The genus Thymus (Thymus L., Lamiaceae L.) is polymorphic, containing various races and forms with minor morphological differences. Up to 200 species have been identified in the world, of which up to 50 are found in Ukraine. Widespread wild essential oil species of the genus Thymus L. in Ukraine are: creeping thyme, Crimean thyme, Dnieper thyme, Marshall’s thyme, flea thyme, Pallas’s thyme. Successfully cultivated: common thyme, Spanish white thin thyme, Spanish white flowering thyme, creeping thyme, lemon thyme. Thyme is known for its rich chemical composition. Carotenoids and chlorophylls contribute to the accumulation of essential oil, polyphenolic compounds, antioxidant, detoxification and radioprotective effects. For the standardization of raw materials of Thymus L. species, it is advisable to determine the accumulation of carotenoids and chlorophylls during the reproductive period. The purpose of the work is to identify and determine the quantitative content of carotenoids and chlorophylls during the reproductive period in the herb species of the genus Thymus L. of the flora of Ukraine. Raw materials were collected in steppe biocenoses and specialized farms of southeastern Ukraine during the reproductive period (May–September 2018–2023) according to generally accepted methods. They were dried at 35 ºС to a moisture content of no more than 10%. n-Hexane extracts (1:100) were used to identify substances and establish their quantitative content. The determination was made by thin-layer chromatography (TLC) followed by densitometry and spectrophotometry. By the methods of thin-layer chromatography and spectrophotometry in n-hexane extracts from grass species of the genus Thymus L. of flora of Ukraine 4 carotenoids and 2 chlorophylls were identified. Cultivated species had the highest content: Th. vulgaris L. and Th. x citriodorus (Pers.) Schreb. var. «Silver Queen». The accumulation of carotenoids and chlorophylls in the raw materials of the genus Thymus L. during the reproductive period was studied. The results indicate the expediency of standardization of the studied raw materials according to the accumulation of carotenoids and chlorophylls. Рід чебрець (Thymus L., Lamiaceae L.) є поліморфним, містить різноманітні раси та форми з дрібними морфологічними відмінностями. У світі ідентифіковано до 200 видів, з яких в Україні трапляються до 50. Розповсюдженими дикорослими ефіроолійними видами роду Thymus L. в Україні є: чебрець повзучий, ч. кримський, ч. дніпровський, ч. Маршаллів, ч. блошиний, ч. Палласів. Успішно культивуються: чебрець звичайний, ч. іспанський білий тонкий, ч. іспанський білий квітучий, ч. повзучий, ч. лимонний. Чабрець відомий багатим хімічним складом. Каротиноїди та хлорофіли сприяють накопиченню ефірної олії, поліфенольних сполук, антиоксидантній, детоксикаційній та радіопротекторній дії. Для стандартизації сировини видів роду Thymus L. доцільним є визначення накопичення каротиноїдів і хлорофілів протягом репродуктивного періоду. Мета роботи – ідентифікація та визначення кількісного вмісту каротиноїдів та хлорофілів у репродуктивний період у траві видів роду Thymus L. флори України. Сировину збирали у степових біоценозах та спеціалізованих господарствах південно-східної України під час репродуктивного періоду (травень–вересень 2018–2023 рр.) за загальноприйнятими методиками. Висушували за температури 35 ºС та вологості не більше 10%. Для ідентифікації речовин та встановлення їх кількісного вмісту використовували н-гексанові витяги (1:100). Визначення здійснювали методами тонкошарової хроматографії з наступною денситометрією та спектрофотометрії. Методами тонкошарової хроматограми та спектрофотометрії в н-гексанових витягах із трави видів роду Thymus L. флори України ідентифіковано 4 каротиноїди та 2 хлорофіли. Найбільший вміст був притаманний культивованим видам: Th. vulgaris L. та Th. х citriodorus (Pers.) Schreb. var. «Silver Queen». Досліджено накопичення каротиноїдів та хлорофілів у сировині роду Thymus L. у репродуктивний період. Результати свідчать про доцільність стандартизації досліджуваної сировини за накопиченням каротиноїдів та хлорофілів.
Дослідження вмісту каротиноїдів та хлорофілів у траві ефіроолійних видів роду Thymus L. У репродуктивний період
О. V. Mazulin - http://orcid.org/0000-0003-0628-4457; L. А. Fukleva - https://orcid.org/0000-0002-2930-0619; Y. M. Steshenko - http://orcid.org/0000-0002-7538-6740; G. V. Mazulin - http://orcid.org/0000-0002-4227-7388); L. O. Puchkan - http://orcid.org/0000-0003-4338-6268.
Keywords: species of the genus Thymus; herb; essential oils; carotenoids; chlorophylls; quantitative content; methods of thin-layer chromatography and spectrophotometry; reproductive period; види роду Чебрець; трава; ефірні олії; каротиноїди; хлорофіли; кількісний вміст; методи тонкошарової хроматографії та спектрофотометрії; репродуктивний період